Influence of oxygenation time on crack growth in titanium alloy under cyclic bending - Rozumek, D.; Hepner, M. (Фізико-хімічна механіка матеріалів, 2011)
The paper contains the results of tests on the fatigue crack growth in Ti–6Al–4V titanium alloy. Plane specimens of 4 mm in thickness with a unilateral notch were used. An analysis of crack growth was carried out for specimens without and after 2 and 4 h oxygenation process as well as fatigue crack growth rate was determined. From the test results it appears that the fatigue crack growth in the specimens without thermo-chemical treatment differs from the fatigue crack growth in the specimens after oxygenation. It has been also found that the applied surface treatment increases fatigue life of the considered alloy. Досліджено втомний ріст тріщин у титановому сплаві Ti–6Al–4V у вихідному стані та після високотемпературного насичення киснем на плоских зразках товщиною 4 mm з одностороннім боковим надрізом за навантаження згином. Виконано фрактографічний аналіз особливостей втомного росту тріщини і визначено її швидкість для різних станів металу: у вихідному та після 2 і 4 h насичення киснем. Виявлено, що хімікотермічна обробка впливає на втомний ріст тріщини, при цьому підвищується втомна довговічність. Исследован усталостный рост трещин в титановом сплаве Ti–6Al–4V в исходном состоянии и после высокотемпературного насыщения кислородом на плоских образцах толщиной 4 mm с односторонним боковым надрезом при нагружении изгибом. Проведен фрактографический анализ особенностей усталостного роста тещин и определена её скорость для разных состояний металла: в исходном и после 2 и 4 h насыщения кислородом. Выявлено, что химико-термическая обработка влияет на усталостный рост трещин, при этом повышается усталостная долговечность.